What role does land consolidation play in the multi-dimensional rural revitalization in China? A research synthesis. (September 2022) - Yin, Qiqi; Sui, Xueyan; Ye, Bei; Zhou, Yujie; Li, Chengqiang; Zou, Mengmeng; Zhou, Shenglu
Abstract: With the rural revitalization strategy was proposed in 2017, large-scale land consolidation has been carried out in rural areas of China, which has profoundly impacted rural development and sustainability. To assess the multi-dimensional effects of land consolidation on rural revitalization, an evaluation system was constructed following the proposed "target-indicator-outcome" framework and subsequently applied to 193 cases documented in 92 peer-reviewed articles for a systematic review and meta-analysis. The results indicate that rural land consolidation had played more positive than no/negative roles in facilitating rural revitalization, with cases reporting generally positive outcomes accounting for 74%. Considering four targets of rural revitalization, positive effects were statistically significant in the case of Prosperous Life and Industrial Prosperity, with positive cases accounting for 86% and 79%. However, the positive effects in terms of Ecological Livability and Rural Civilization & Effective Governance is statistically non-significant, with positive cases accounting for 65% and 47%. In terms of 12 indicators, an overview of the positive and no/negative effects brought by land consolidation were summarized. The cases of the indicators related to rural producting and living were largely positive, however, the indicators related to rural ecology, rural civilization and governance reported higher no/negative outcomes. From the perspective of spatial differentiation, the positive effects were significant in eastern, central and western China, and the proportion of positive cases in eastern China (80%) and western China (77%) were higher than those in central China (67%). The opportunities and threats of rural land consolidation in multi-dimension deserve policy attention in rural revitalization strategy. Graphical Abstract: ga1 Highlights: This study provides a synthetic evaluation of land consolidation effects on rural revitalization in China. Land consolidation played more positive than no/negative roles in rural revitalization, with positive cases accounting for 74%. More positive outcomes were reported significantly in the case of Prosperous Life and Industrial Prosperity. The positive effects were non-significant in terms of Ecological Livability and Rural Civilization & Effective Governance.